Code-Switching Models Used by Millennial Muslim Preachers on Instagram in Indonesia: An Analysis from a Grammatical Perspective - Anam, Moh Khoirul; Tsania, Farrah Nur; Safinatunnajah, Jihan; Zainal Mukhlis; Isna Laili Qurroti A'yun (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
Code-switching is becoming increasingly prevalent among young people as a communication strategy that reflects contemporary social and cultural dynamics. Millennial Muslim preachers in Indonesia are also utilizing code-switching to convey their messages, particularly through the Instagram platform. This study aims to identify the code-switching models used by millennial Muslim preachers from a grammatical perspective. Data was collected from the Instagram accounts @hanan_attaki, @syam_elmarusy, @husein_hadar, @adihidayatofficial, and @kohdennislim using purposive sampling. Data analysis was conducted using a grammatical approach in code-switching studies. The results of the study indicate that the types of code-switching used include inter-sentential, intra-sentential, extra-sentential, single-word, and word-internal code-switching. Each account shows different patterns of use, with some displaying only one type and others displaying a combination of several types of code-switching. These findings indicate a high degree of linguistic adaptability among preachers in tailoring religious messages to the characteristics of a young audience. In conclusion, code-switching variation serves as an effective strategy in bridging social gaps and enhancing the connectivity of religious messages in digital media.